Penerapan Artificial Intelligence-ChatGPT dalam Pembelajaran Matematika Diskrit - Silvana Samaray (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
Learning discrete mathematics, particularly on the topic of equivalence in propositional logic using propositional algebra laws, often presents challenges for students due to its abstract nature and the logical thinking skills required. This study aims to analyze the effectiveness of using ChatGPT as a learning aid to enhance students' understanding of this topic. The research employed a quantitative method with a post-test only control group design, involving two groups of students: an experimental group using ChatGPT and a control group utilizing conventional learning methods. Data were collected through a post-learning achievement test. The results showed that the average score of the experimental group (85.47) was significantly higher than that of the control group (66.78). The independent t-test results yielded a significance value of < 0.05, indicating a significant difference in learning outcomes between the two groups. Furthermore, the calculation of Cohen's d showed a value of 0.959, categorized as a large effect size. These findings indicate that the use of ChatGPT as a learning aid has a significant impact on students' learning outcomes. With its interactive and responsive features, ChatGPT helps students grasp complex propositional logic material more easily. This study recommends utilizing AI-based technologies like ChatGPT as an innovative learning strategy, particularly for abstract topics in discrete mathematics.